Climate and land cover effects on the temperature of Puget Sound streams. Issue 13 (6th March 2016) - Cao, Qian; Sun, Ning; Yearsley, John; Nijssen, Bart; Lettenmaier, Dennis P.
Abstract: We apply an integrated hydrology‐stream temperature modeling system, DHSVM‐RBM, to examine the response of the temperature of the major streams draining to Puget Sound to land cover and climate change. We first show that the model construct is able to reconstruct observed historic streamflow and stream temperature variations at a range of time scales. We then explore the relative effect of projected future climate and land cover change, including riparian vegetation, on streamflow and stream temperature. Streamflow in summer is likely to decrease as the climate warms especially in snowmelt‐dominated and transient river basins despite increased streamflow in their lower reaches associated with urbanization. Changes in streamflow also result from changes in land cover, and changes in stream shading result from changes in riparian vegetation, both of which influence stream temperature. However, we find that the effect of riparian vegetation changes on stream temperature is much greater than land cover change over the entire basin especially during summer low flow periods. Furthermore, while future projected precipitation change will have relatively modest effects on stream temperature, projected future air temperature increases will result in substantial increases in stream temperature especially in summer. These summer stream temperature increases will be associated both with increasing air temperature, and projected decreases in low flows. We find that restoration of riparian vegetation could mitigate much of the projected summer stream temperature increases. We also explore the contribution of riverine thermal loadings to the heat balance of Puget Sound, and find that the riverine contribution is greatest in winter, when streams account for up to 1/8 of total thermal inputs (averaged from December through February), with larger effects in some sub‐basins. We project that the riverine impact on thermal inputs to Puget Sound will become greater with both urbanization and climate change in winter but become smaller in summer due to climate change. Copyright © 2016 John Wiley & Sons, Ltd.